Determinants of the Usage of ChatGPT in the Tourism and Hospitality Industry: A Model Proposal from the Technology Acceptance Perspective - SÖKMEN, Alptekin; ARICI, Hasan Evrim; ÇALIŞKAN, Gürkan (Journal of Tourism and Gastronomy Studies, 2024)
ChatGPT is a generative artificial intelligence technology. It is a technology that is becoming more widely used. This research aimed to identify the determinants of the usage of ChatGPT in the tourism and hospitality industry. For this purpose, a systematic literature review was conducted, and six determinants of ChatGPT usage were identified. These are experience quality, satisfaction, interaction, ethics, reliability, and design features. These determined variables affect the behavioral intention regarding the usage of ChatGPT. Within the scope of the findings, a model for using ChatGPT is proposed from the perspective of the Technology Acceptance Model. Determinants of the use of ChatGPT in the tourism and hospitality industry have been identified. Relevant articles were subjected to thematic analysis and themes were determined. These; quality of experience, satisfaction, interaction, ethics, reliability and design features. In this research, determinants regarding the use of ChatGPT in the tourism and accommodation sector were identified and recommendations were made.
Keywords: 3. Good health